2015
DOI: 10.1038/srep09386
|View full text |Cite
|
Sign up to set email alerts
|

Module organization and variance in protein-protein interaction networks

Abstract: A module is a group of closely related proteins that act in concert to perform specific biological functions through protein–protein interactions (PPIs) that occur in time and space. However, the underlying module organization and variance remain unclear. In this study, we collected module templates to infer respective module families, including 58,041 homologous modules in 1,678 species, and PPI families using searches of complete genomic database. We then derived PPI evolution scores and interface evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 52 publications
(88 reference statements)
1
17
0
Order By: Relevance
“…Lin et al . 39 have found that a topological module usually contains core and ring components and that the major biological function is exerted through core components; thus, it is necessary to consider these core components when detecting functional modules. Furthermore, we also determined that the average shortest path in the modules (i.e., 2.25 in IBGLL) was shorter than that in the pathways (i.e., 3.82 in PID), because topological modules contain only proteins exhibiting dense interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al . 39 have found that a topological module usually contains core and ring components and that the major biological function is exerted through core components; thus, it is necessary to consider these core components when detecting functional modules. Furthermore, we also determined that the average shortest path in the modules (i.e., 2.25 in IBGLL) was shorter than that in the pathways (i.e., 3.82 in PID), because topological modules contain only proteins exhibiting dense interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, certain databases, such as IntAct 15 , BioGRID 16 and DIP 17 , have been established as repositories to collect and organize the reported protein interactions of nonspecific species. Despite these improved protocols and evolved methods, the cost and time requirements of such exploratory experimental studies remain prohibitive, and thus only small to mid-sized PIN studies have been conducted 18 19 . Alternatively, proteomic studies are progressively shifting away from classical approaches that focus on a few proteins toward whole PINs to chart the complex and dynamic interactions in cellular processes.…”
mentioning
confidence: 99%
“…Protein complex is a fundamental unit formed with highly connected proteins and often possesses specific biological functions [ 26 ]. In biology, protein interaction networks (PINs) are not static—they dynamically change over time and are responsive to the stimuli caused by external environment.…”
Section: Discussionmentioning
confidence: 99%